Comparative Study of Tax Incentives in Indonesia, Malaysia, and the United States of America to Support Research and Development - Irwanto Irwanto; Meilani Meilani (Universitas Pelita Harapan Medan Campus, 2022)
Studies found that R&D help promoting a country’s economic growth. It is important for Indonesia to consider this as a long-run solution to escape middle-income trap since Indonesia’s R&D spending has been below 1% every year. Further studies call for tax incentives as a solution to this problem. The purpose of this study is to compare different tax incentives schemes for R&D, along with giving recommendation to implement those. The approach in this study is qualitative descriptive method with literature review and secondary data. Indonesia provides R&D incentives as additional incentives to other schemes such as investment incentive schemes. However, a new regulation has been formed, PP No. 45 Tahun 2019, to provide R&D based tax incentives which gives 300% deduction on eligible R&D expenses. Yet, the eligibility has not been issued until now. R&D based tax incentive schemes in Malaysia have come to a fruitful success for its brink to reaching high-income country status. Malaysia provides 200% deduction for eligible R&D expenses, tax holiday and investment tax allowance for R&D companies and in-house R&D. Contrarily, the US treat eligible R&D expenses as deductible expenses and give tax credit of 20% or below, determined by historical financial data. This study concludes that Indonesia should define R&D for tax purpose, quickly assess which industry and activities are eligible for 300% super deduction and take Malaysia as an example in the assessment. Finally, Malaysia should slowly reduce unfavourable tax incentives, which are losing potential income, and give other tax incentives which can be a win-win solution to both parties. Keywords: Tax. Incentives, Research and Development, Innovation, Economic Growth, Indonesia, Malaysia, the United States of America.